Empathy and Patterns of Empathy Development in School Counselor Candidate - Tri Sutanti; Agungbudiprabowo Agungbudiprabowo; Ariadi Nugraha (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
The purpose of this study was to find out empathy and the form of instilling empathy in prospective counselors. This descriptive quantitative study involved 174 first-semester students of the guidance and counseling department at Ahmad Dahlan University, recruited using a purposive sampling technique. Data were collected using an empathy scale developed from the IRI Davis scale (1983) and a questionnaire on empathy cultivation patterns which contained statements about the empathy inculcation patterns that students received from their parents or guardians. The data were analyzed descriptively, showing that prospective counselors’ empathy was mostly in the moderate category.   The pattern of inculcation of empathy is given by parents or guardians in the induction pattern. In terms of the empathy cultivation pattern, moral advice was found to be the most frequent means for instilling empathy.  This study highlights the need for developing a counseling strategy that emphasizes moral advice in a fun counseling activity and discussion dynamics that adapts to adolescent development.